The Influence of Work Discipline, Work Motivation, and Work Environment on Turnover Intention (Study on Employees of CV. Harmoni Jaya Sentosa) - Awaluddin Nurramdhani; Dedi Gumilar; Astrin Kusumawardani; Listri Herlina; Muhammad Ihsan Muchta (Komunitas Dosen Indonesia, 2024)
The corporate sector faces a significant challenge in employee turnover, notably in Indonesia and other Southeast Asian nations. This article discusses the issue of CV Harmoni Jaya Sentosa, an Indonesian firm, having excessive personnel turnover. A high staff turnover rate and delay are two of the signs associated with this phenomenon. A large amount of employees leave their positions each month, according to the data provided by the organisation. A combination of descriptive and verification procedures, as well as quantitative tools, were utilised in the study. In addition to receiving information from secondary sources, we also obtained information from business records, questionnaires, and in-person interviews. To analyse the data, statistical methods were utilised. Furthermore, the analysis findings, which were based on a significance level of 0.05, indicate that work environment and discipline have a significant relationship with turnover intention. On the other hand, work motivation and turnover intention do not have an important relationship at the level of significance that was specified. The findings of this study give the organisation's management with valuable information regarding how they may regulate the variables that determine the degree to which an employee wishes to resign. Work discipline and the environment of the workplace may be crucial determinants, even though work motivation does not have a substantial impact on the intention to leave the company.